2018
DOI: 10.1093/mnras/sty1755
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on the nuclear equation of state and the neutron star structure from crustal torsional oscillations

Abstract: We systematically examine torsional shear oscillations of neutron star crusts by newly taking into account the possible presence of the phase of cylindrical nuclei. In this study, we neglect an effect of magnetic fields, under which the shear oscillations can be damped by the magnetic interaction. First, by identifying the low frequency quasiperiodic oscillations (QPOs) observed in the soft-gamma repeaters (SGRs) as the fundamental torsional oscillations, we constrain the slope parameter of the nuclear symmetr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 72 publications
4
51
0
Order By: Relevance
“…We can thus conclude that light neutron star models are favored over heavy ones in our identification. Incidentally, the (M, R) = (1.3M⊙, 13km) case is consistent with the neutron star models considered to be relevant as a result of the comparison of the constraint on K0, which is obtained by assuming that the lowest overtone frequency in the sphere-cylinder layer is equal to the QPO frequency of 626.5 Hz observed from SGR 1806-20, with the terrestrial constraint on K0 (Sotani, Iida & Oyamatsu 2018). Furthermore, the (M, R) = (1.3M⊙, 13km) case is consistent with the mass and radius formulas for low-mass neutron stars , given the optimal value of L ∼ 70 MeV, and also with the constraint on the mass and radius of each of the merging binary neutron stars (Abbott et al 2018).…”
Section: Torsional Oscillation Frequencies and Comparison With Qpossupporting
confidence: 80%
See 2 more Smart Citations
“…We can thus conclude that light neutron star models are favored over heavy ones in our identification. Incidentally, the (M, R) = (1.3M⊙, 13km) case is consistent with the neutron star models considered to be relevant as a result of the comparison of the constraint on K0, which is obtained by assuming that the lowest overtone frequency in the sphere-cylinder layer is equal to the QPO frequency of 626.5 Hz observed from SGR 1806-20, with the terrestrial constraint on K0 (Sotani, Iida & Oyamatsu 2018). Furthermore, the (M, R) = (1.3M⊙, 13km) case is consistent with the mass and radius formulas for low-mass neutron stars , given the optimal value of L ∼ 70 MeV, and also with the constraint on the mass and radius of each of the merging binary neutron stars (Abbott et al 2018).…”
Section: Torsional Oscillation Frequencies and Comparison With Qpossupporting
confidence: 80%
“…1, we illustrate the profile of the shear modulus inside the tube and bubble phases for neutron star models constructed from the first three sets of the OI-EOSs listed in Table 1. From this figure, one can observe that the shear modulus becomes discontinuous at the transition between the tube and bubble phases, which is similar to the case of the transition between the phases of spherical and cylindrical nuclei (Sotani, Iida & Oyamatsu 2018). In addition, it is to be noted that the shear modulus in the tube phase can decrease as the density increases and that this tendency becomes stronger for larger L. This tendency may well come from the decrease of the volume fraction of a gas of dripped neutrons with density (e.g., Watanabe & Iida (2003)).…”
Section: Shear Modulussupporting
confidence: 71%
See 1 more Smart Citation
“…On the crust equilibrium, the frequency of torsional oscillations can be determined by solving the eigenvalue problem. The concrete perturbation equation and boundary conditions for torsional oscillations can be seen in Sotani et al () and Sotani et al (, ). In Figure , we show the ℓ = 2 fundamental frequency of the torsional oscillations excited in the phase of tube and bubble as a function of L , where the marks denote the results obtained with various sets of EOS parameters.…”
Section: Torsional Oscillations and Identification Of Qposmentioning
confidence: 99%
“…On the other hand, we have already shown that the fundamental frequency excited in the phase of spherical and cylindrical nuclei can be fitted with the different functional form of L (Sotani et al , , , ; Sotani et al ). In addition, we could constrain L as L ≃ 58 − 73 MeV by identifying the 626.5 Hz QPO in SGR 1806‐20 as the first overtone of torsional oscillation with the help of the terrestrial constraint on K 0 , where we also showed that relatively low mass neutron star models are favored more from the experimental constraints and QPO observations (Sotani et al ).…”
Section: Torsional Oscillations and Identification Of Qposmentioning
confidence: 99%